Variability of urban drainage area delineation and runoff calculation with topographic resolution and rainfall volume. (11th March 2023) - Sokolovskaya, Natalya; Vaughn, Casey; Jahangiri, Humaira; Smith, Virginia; Wadzuk, Bridget; Ebrahimian, Ali; Nyquist, Jonathan
Abstract: Designing green stormwater infrastructure (GSI) requires an accurate estimate of the contributing drainage area and a model for runoff generation. We examined some factors that add to the uncertainty associated with these two design steps in the urban environment. Delineated drainage areas at five GSI sites in southeastern Pennsylvania (PA) were compared for digital elevation model (DEM) resolutions (grid cell sizes) ranging from 8 to 300 cm. The findings point to an optimal DEM resolution range of 30–60 cm, with up to 100 cm resolution providing acceptable results for some sites. The delineated areas were validated with the observed flow and rainfall records at three sites by examining curve number (CN) values calculated for individual storms. The calculated CNs decreased with increasing rainfall volume, which supports a recommendation to consider a range of CNs in the GSI design process. The variation in calculated CNs was higher for the overestimated drainage areas derived from coarser DEM resolutions. We hypothesize that the observed continued decrease of CNs at high rainfall is the result of inlet bypass, a potentially significant factor in urban hydrology. The findings from this study provide insight into the variability in expected delineated drainage areas using standard methods in GSI design. HIGHLIGHTS: Evaluate the optimal DEM resolution for urban drainage area delineation. Inform design decisions for urban green stormwater infrastructure. Validate area delineation with observed flows and the curve number method.